The Logic of Inhibitory Connectivity in the Neocortex - Fino, Elodie (2012)
Although inhibition plays a major role in the function of the mammalian neocortex, the circuit connectivity of GABAergic interneurons has remained poorly understood. The authors review recent studies of the connections made to and from interneurons, highlighting the overarching principle of a high density of unspecific connections in inhibitory connectivity. Whereas specificity remains in the subcellular targeting of excitatory neurons by interneurons, the general strategy appears to be for interneurons to provide a global “blanket of inhibition” to nearby neurons. In the review, the authors highlight the fact that the function of interneurons, which remains elusive, will be informed by understanding the structure of their connectivity as well as the dynamics of inhibitory synaptic connections. In a last section, the authors describe briefly the link between dense inhibitory networks and different interneuron functions described in the neocortex.